2022
DOI: 10.1038/s41559-022-01699-x
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic muscle splitting patterns reveal homologies of amniote forelimb muscles

Abstract: Limb muscles are remarkably complex and evolutionarily labile. Although their anatomy is of great interest for studies of the evolution of form and function, their homologies among major amniote clades have remained obscure. Studies of adult musculature are inconclusive owing to the highly derived morphology of modern amniote limbs, but correspondences become increasingly evident earlier in ontogeny. We followed the embryonic development of forelimb musculature in representatives of six major amniote clades an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(41 citation statements)
references
References 63 publications
0
41
0
Order By: Relevance
“…While there are overlaps between the muscles involved in flipper twisting employed by C. eurymerus, C. caretta, and Z. californianus, there appear to be more difference between them. A certain degree of similarity is unsurprising, because limb muscles are highly conservative across amniotes (Smith-Paredes et al, 2022). Therefore, with the help of AnNA and muscle function evaluation, we were able to describe the convergent evolution of flipper twisting in C. eurymerus, C. caretta, Z. californianus, and S. demersus.…”
Section: Modularitymentioning
confidence: 99%
“…While there are overlaps between the muscles involved in flipper twisting employed by C. eurymerus, C. caretta, and Z. californianus, there appear to be more difference between them. A certain degree of similarity is unsurprising, because limb muscles are highly conservative across amniotes (Smith-Paredes et al, 2022). Therefore, with the help of AnNA and muscle function evaluation, we were able to describe the convergent evolution of flipper twisting in C. eurymerus, C. caretta, Z. californianus, and S. demersus.…”
Section: Modularitymentioning
confidence: 99%
“…Problematically, many of the aforementioned studies'' interpretations provided little (if any) justification, and sometimes were framed without consideration of the anatomy of extant species, relying more on geometric arguments. Most prior studies were also founded upon now‐outdated hypotheses of homology (Diogo et al, 2016; Smith‐Paredes et al, 2022). Collectively, this has repeatedly resulted in conflicting assessments of muscular anatomy, and, in turn, locomotor function and its evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Irrespective of specific ecological adaptations, the musculoskeletal anatomy of the mammalian forelimb is, in general, highly distinctive among extant tetrapods, including the reduction or total loss of most pectoral girdle bones, well‐developed processes for muscle attachment (e.g., olecranon of the ulna), dorsal translocation of ventral muscle masses proximally, and extensive muscular differentiation distally (Diogo et al, 2016; Gregory & Camp, 1918; Romer, 1922, 1962). At least therian mammals also exhibit a unique sequence of embryonic development (Cheng, 1955; Smith‐Paredes et al, 2022). Understanding the deep evolutionary history of mammalian forelimb musculature can provide important context for exploring how and why these distinctive traits evolved, and how this may have shaped the diversification of forelimb functions.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, this information is indispensable for estimating the range of motion and function of muscles. However, it is also known that attachment sites in the limbs of tetrapods vary greatly among species to allow for a variety of locomotion [ 5 ]. In other words, although information regarding muscle attachment site is useful for estimating muscle function, it is not sufficient by itself as a criterion for muscle identification.…”
Section: Introductionmentioning
confidence: 99%
“…Developmental biological studies have shown that normal muscular development and differentiation are strongly dependent on neural activities [9][10][11]. In early stage of musculogenesis, the passage of nerves strongly contributes to the separation of the muscle mass [5]. The separated muscle mass is then further subdivided to form individual muscles, and since there is specificity between the nerves and muscles [11], information about innervation is essential to establish the identity of the muscle.…”
Section: Introductionmentioning
confidence: 99%